Novel 4, 8-benzobisthiazole copolymers and their field-effect transistor and photovoltaic applications. Issue 45 (13th November 2017) - Conboy, Gary; Taylor, Rupert G. D.; Findlay, Neil J.; Kanibolotsky, Alexander L.; Inigo, Anto R.; Ghosh, Sanjay S.; Ebenhoch, Bernd; Krishnan Jagadamma, Lethy; Thalluri, Gopala Krishna V. V.; Sajjad, Muhammad T.; Samuel, Ifor D. W.; Skabara, Peter J.
Abstract : A series of BBT-containing copolymers featuring the 4, 8-conjugation pathway is presented and evaluated. Abstract : A series of copolymers containing the benzo[1, 2- d :4, 5- d ′]bis(thiazole) (BBT) unit has been designed and synthesised with bisthienyl-diketopyrrolopyrrole (DPP), dithienopyrrole (DTP), benzothiadiazole (BT), benzodithiophene (BDT) or 4, 4′-dialkoxybithiazole (BTz) comonomers. The resulting polymers possess a conjugation pathway that is orthogonal to the more usual substitution pathway through the 2, 6-positions of the BBT unit, facilitating intramolecular non-covalent interactions between strategically placed heteroatoms of neighbouring monomer units. Such interactions enable a control over the degree of planarity through altering their number and strength, in turn allowing for tuning of the band gap. The resulting 4, 8-BBT materials gave enhanced mobility in p-type organic field-effect transistors of up to 2.16 × 10 −2 cm 2 V −1 s −1 forpDPP2ThBBT and good solar cell performance of up to 4.45% power conversion efficiency forpBT2ThBBT .